2010
DOI: 10.1002/pssa.201026120
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of individual ZnMgO nanowires synthesized by a vapor‐transport method

Abstract: ZnMgO nanowires are synthesized on Si substrates using a vapor-transport method and their structural and luminescent characteristics are investigated using various techniques. The shift of the (002) peak in the X-ray diffraction measurements and the blue shift of the near-band-edge emission peak in the photoluminescence measurements of the ZnMgO samples are consistent with the incorporation of the small amount of Mg ($5 at.%) in ZnO. Individual ZnMgO nanowires are also investigated for their structural and lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Chakrabarti et al [20] have also reported on XRD peaks that could be indexed to a hexagonal wurtzite ZnO structure and decreased in both a and c cell parameters of Mg-doped ZnO for x values from 0 to 0.15. A shift in the XRD peaks of Mg-doped ZnO is found by Zhuang et al [16] and Haiping Tang et al [1]. C axis contraction of Mg-doped ZnO has been presented by Kumar et al [11], Wang et al [15], and Wang et al [14].…”
Section: Xrd and Rietveld Refinement Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Chakrabarti et al [20] have also reported on XRD peaks that could be indexed to a hexagonal wurtzite ZnO structure and decreased in both a and c cell parameters of Mg-doped ZnO for x values from 0 to 0.15. A shift in the XRD peaks of Mg-doped ZnO is found by Zhuang et al [16] and Haiping Tang et al [1]. C axis contraction of Mg-doped ZnO has been presented by Kumar et al [11], Wang et al [15], and Wang et al [14].…”
Section: Xrd and Rietveld Refinement Analysismentioning
confidence: 89%
“…Recently, various nanostructures of zinc oxide (ZnO) have attracted global interest and led to active research activities with possible applications in electronic, optoelectronic, and energy-conversion devices [1]. ZnO is an excellent electronic and photonic material having a wide band gap (E g ≈ 3.27 eV) and a large exciton binding energy of 60 meV.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NWs used for this experiment were prepared by vapor‐phase transport 21 with a carbothermal reduction process in a dual‐tube low‐pressure chemical vapor deposition (LPCVD) system as previously reported 22, 23. A 1:1 mixture of pure ZnO (0.5 g, Aldrich, 99.99%) and graphite powder (0.5 g, Sigma–Aldrich, particle size ≤20 µm) is used as a source material and Si wafer with 200‐nm thick SiO 2 is employed as a substrate.…”
Section: Methodsmentioning
confidence: 99%
“…46 Substitutional doping of Mg with ZnO, on the other hand, has been described as a means of engineering the bandgap of a ternary Zn x Mg 1– x O system as high as a 5.8 eV for solar-blind photodetectors. 710 Although Mg has been reported as a feasible dopant to ZnO (due to the similar ionic radii of Zn 2+ and Mg 2+ ), 11,12 Mg/ZnO alloy systems have also shown to phase segregate for high Mg content. 13 Thus, the development of reliable techniques toward synthesizing aligned ZnO nanowires, and appreciably incorporating Mg during synthesis is of great significance.…”
Section: Introductionmentioning
confidence: 99%